A Regular D‑optimal Weighing Design with Negative Correlations of Errors - Graczyk, Małgorzata; Ceranka, Bronisław (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The issues concerning optimal estimation of unknown parameters in the model of chemical balance weighing designs with negative correlated errors are considered. The necessary and sufficient conditions determining the regular D‑optimal design and some new construction methods are presented. They are based on the incidence matrices of balanced incomplete block designs and balanced bipartite weighing designs.